Negative electrode material for lithium ion secondary battery, evaluation method thereof and manufacturing method thereof, negative electrode for lithium ion secondary battery, and lithium ion secondary battery
The use of graphite particles with a specific springback ratio and compressive load in the negative electrode material of lithium-ion secondary batteries addresses the issue of reduced cycle characteristics due to decreased electrolyte contact, resulting in improved liquid absorption and maintained cycle performance.
Patent Information
- Application Number
- JP2022578544
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-02-01
- Filing Date
- 2022-02-01
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2042-02-01
AI Technical Summary
In lithium-ion secondary batteries, the gaps between active material particles disappear during repeated charging and discharging, leading to reduced cycle characteristics due to increased cell resistance and decreased electrolyte contact.
A negative electrode material composed of graphite particles with a specific springback ratio and compressive load, satisfying the formula [Springback ratio x 7.6] + [Compression load (kN/cm^2)] ≥ 4.2, which improves liquid absorption properties and maintains cycle characteristics.
The proposed negative electrode material enhances the liquid absorption of the negative electrode, thereby improving the cycle characteristics of lithium-ion secondary batteries by maintaining the electrolyte contact and reducing cell resistance.
Smart Images

Figure 0007661983000001 
Figure 0007661983000002 
Figure 0007661983000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a negative electrode material for a lithium ion secondary battery, an evaluation method and a manufacturing method thereof, a negative electrode for a lithium ion secondary battery, and a lithium ion secondary battery. [Background technology]
[0002] Taking advantage of their characteristics of small size, light weight, and high energy density, lithium-ion secondary batteries have been widely used in electronic devices such as notebook personal computers (PCs), mobile phones, smartphones, tablet PCs, etc. In recent years, against the backdrop of environmental issues such as global warming caused by CO2 emissions, clean electric vehicles (EVs) that run only on batteries, hybrid electric vehicles (HEVs) that combine gasoline engines with batteries, plug-in hybrid electric vehicles (PHEVs), and other electric vehicles have become widespread, and the development of lithium-ion secondary batteries (automotive lithium-ion secondary batteries) to be installed in these vehicles is underway.
[0003] The input characteristics of lithium-ion secondary batteries are greatly affected by the performance of the negative electrode material of the lithium-ion secondary battery. Carbon materials are widely used as materials for the negative electrode material of lithium-ion secondary batteries. For example, carbon materials with high crystallinity, such as artificial graphite and spherical natural graphite, which is made by spheroidizing scaly natural graphite, have been proposed as materials for obtaining high-density negative electrodes.
[0004] As an example of artificial graphite, Patent Document 1 discloses a negative electrode material for lithium ion secondary batteries that includes composite particles containing a plurality of flat graphite particles that are aggregated or bonded so that their oriented planes are non-parallel, and spherical graphite particles. Patent Document 2 discloses a negative electrode active material for lithium secondary batteries that includes carbon powder particles that have a morphology in which plate-like particles are oriented and stacked along their planes to be assembled into a primarily stable structure, and that have micropores formed on the surface. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2015 / 147012 [Patent Document 2] JP 2005-302725 A Summary of the Invention [Problem to be solved by the invention]
[0006] In lithium-ion secondary batteries, the voids between the active material particles disappear during repeated charging and discharging, resulting in the appearance of areas where the electrolyte and the active material cannot come into contact. As a result, the cell resistance increases, causing a decrease in cycle characteristics such as the cycle capacity retention rate.
[0007] In view of the above circumstances, an object of the present disclosure is to provide a negative electrode material for lithium ion secondary batteries that enables the production of lithium ion secondary batteries with excellent cycle characteristics, an evaluation method and a production method thereof, and a negative electrode for lithium ion secondary batteries and a lithium ion secondary battery produced using the negative electrode material. [Means for solving the problem]
[0008] Means for solving the above problems include the following aspects. <1> A negative electrode material for lithium-ion secondary batteries, which is graphite particles that satisfy the following formula (1): [Springback rate x 7.6] + [Compressive load (kN / cm 2 )]≧4.2 (1) <2> The graphite particles are compressed with a load of 2.0 kN / cm 2 That's all. <1> The negative electrode material for lithium ion secondary batteries according to claim 1. <3> The springback rate of the graphite particles is 0.25 or more. <1> or <2> The negative electrode material for lithium ion secondary batteries according to claim 1. <4> The graphite particles include composite particles having a structure in which a plurality of flat graphite particles are stacked. <1> ~ <3> 10. The negative electrode material for a lithium ion secondary battery according to claim 9, <5> The springback rate of graphite particles, which are negative electrode materials for lithium-ion secondary batteries, and the compression load (kN / cm 2 ) as explanatory variables and a liquid absorption time of a negative electrode containing the negative electrode material for a lithium ion secondary battery as an objective variable, to evaluate a negative electrode material for a lithium ion secondary battery by using a regression equation obtained by multiple regression analysis. <6> <5> 2. A method for producing a negative electrode material for a lithium ion secondary battery, which produces a negative electrode material for a lithium ion secondary battery based on an evaluation result of the negative electrode material for a lithium ion secondary battery using the evaluation method for a negative electrode material for a lithium ion secondary battery described in claim 1. <7> <1> ~ <4> A method for producing a negative electrode material for a lithium ion secondary battery according to any one of claims 1 to 4, A method for producing a negative electrode material for a lithium-ion secondary battery, comprising the step of graphitizing coke. <8> The thermal expansion coefficient of the coke after firing at 1400°C is 2.30×10 -6 / ℃ or more <7> A method for producing the negative electrode material for lithium ion secondary batteries according to claim 1. <9> <1> ~ <4> 13. A negative electrode for a lithium ion secondary battery comprising: a negative electrode material layer containing the negative electrode material for a lithium ion secondary battery according to any one of 1 to 22; and a current collector. <10> <7> A lithium ion secondary battery comprising the negative electrode for lithium ion secondary batteries according to claim 1, a positive electrode, and an electrolyte solution. Effect of the Invention
[0009] According to the present disclosure, there are provided a negative electrode material for lithium ion secondary batteries capable of producing lithium ion secondary batteries with excellent cycle characteristics, an evaluation method and a production method thereof, and a negative electrode for lithium ion secondary batteries and a lithium ion secondary battery produced using the negative electrode material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, the embodiment for carrying out the present invention will be described in detail. However, the present invention is not limited to the following embodiment. In the following embodiment, the components (including element steps, etc.) are not essential unless specifically stated. The same applies to the numerical values and their ranges, and they do not limit the present invention.
[0011] In the present disclosure, the term "step" includes not only a step that is independent of other steps, but also a step that cannot be clearly distinguished from other steps as long as the purpose of the step is achieved. In the present disclosure, a numerical range indicated using "~" includes the numerical values before and after "~" as the minimum and maximum values, respectively. In the numerical ranges described in the present disclosure in stages, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value of the numerical range may be replaced with a value shown in the examples. In the present disclosure, each component may contain multiple types of the corresponding substance. When multiple substances corresponding to each component are present in the composition, the content or amount of each component means the total content or amount of the multiple substances present in the composition, unless otherwise specified. In the present disclosure, multiple types of particles corresponding to each component may be included. When multiple types of particles corresponding to each component are present in the composition, the particle size of each component means the value for a mixture of the multiple types of particles present in the composition, unless otherwise specified. In the present disclosure, the terms "layer" and "film" include cases where the layer or film is formed over the entire area when the area in which the layer or film is present is observed, as well as cases where the layer or film is formed over only a portion of the area. In this disclosure, the term "lamination" refers to stacking layers, where two or more layers may be bonded together or two or more layers may be removable.
[0012] In the present disclosure, the particle size distribution of the negative electrode material and the primary particles contained in the composite particles can be measured by a laser diffraction particle size distribution measuring device. The average particle size of the particles is the particle size (D50) when the cumulative total from the small diameter side in the volumetric particle size distribution is 50%. D90 is the particle size when the cumulative total from the small diameter side in the volumetric particle size distribution is 90%, and D10 is the particle size when the cumulative total from the small diameter side in the volumetric particle size distribution is 10%.
[0013] <Negative electrode material for lithium-ion secondary batteries> The negative electrode material for lithium ion secondary batteries (hereinafter also simply referred to as the negative electrode material) of the present disclosure is graphite particles that satisfy the following formula (1). [Springback rate x 7.6] + [Compressive load (kN / cm 2 )]≧4.2 (1)
[0014] The inventors have focused on the fact that, in the process of repeatedly charging and discharging a lithium-ion secondary battery, the gaps between the graphite particles disappear, resulting in the generation of portions where the electrolyte and the negative electrode active material cannot come into contact, which causes a decrease in the liquid absorption of the negative electrode and a decrease in the cycle capacity retention rate. It is believed that if the electrolyte can easily flow through the negative electrode even when the lithium-ion secondary battery is repeatedly charged and discharged, and the liquid absorption of the negative electrode can be improved, the decrease in the cycle capacity retention rate can be suppressed and the cycle characteristics can be improved.
[0015] In consideration of the above, the present inventors have investigated the properties of the negative electrode material and the properties of the negative electrode that contribute to the liquid absorption of the negative electrode. As a result, they have found that the combination of the springback rate of the graphite particles, which are the negative electrode material, and the compressive load has a strong correlation with the liquid absorption.
[0016] The inventors have found that by adjusting the combination of the springback rate and compression load of the graphite particles within an appropriate range, i.e., by making the graphite particles satisfy the above-mentioned formula (1), the liquid absorption of the negative electrode can be improved and the cycle characteristics of the lithium ion secondary battery can be easily maintained at a good level.
[0017] The reason why the combination of the springback rate of the graphite particles and the compressive load has a strong correlation with the liquid absorption property is not necessarily clear, but can be considered as follows.
[0018] A large compression load on the graphite particles means that the graphite particles are not easily deformed by compression. Therefore, when the compression load on the graphite particles is large, the voids between the graphite particles are not easily eliminated, and in the negative electrode containing the graphite particles, a flow path through which the electrolyte passes is suitably secured, and the occurrence of a portion where the electrolyte and the negative electrode active material cannot contact each other is suppressed.
[0019] A large springback rate of graphite particles means that the graphite particles are not easily broken or destroyed by compression. Therefore, when the springback rate of graphite particles is large, a part of the graphite particles is not easily destroyed, and the voids between the graphite particles are not easily lost. As a result, in a negative electrode containing these graphite particles, a flow path through which the electrolyte passes is suitably secured, and the occurrence of a part where the electrolyte and the negative electrode active material cannot contact each other is suppressed.
[0020] From the above, it is believed that the combination of the springback rate and compressive load of the graphite particles is strongly correlated with the liquid absorption, and that improving the springback rate and compressive load of the graphite particles improves the liquid absorption of the negative electrode.
[0021] (Compressive load) The compressive load of the graphite particles is not particularly limited as long as the graphite particles can satisfy the above-mentioned formula (1). For example, the compressive load of the graphite particles is set to 2.0 kN / cm from the viewpoint of suppressing deformation of the graphite particles due to pressing during the preparation of the negative electrode and from the viewpoint of further improving the cycle characteristics of the lithium ion secondary battery. 2 It is preferable that the resistance is 2.4 kN / cm or more. 2 More preferably, it is 2.8 kN / cm or more. 2 More preferably, it is 3.0 kN / cm or more. 2 More preferably, it is equal to or greater than this.
[0022] In order to prevent deformation of the current collector caused by pressing during the production of the negative electrode and peeling of the current collector from the active material, the compression load of the graphite particles was set to 4.5 kN / cm. 2 may be less than 4.3 kN / cm 2 It may be less than 4.0 kN / cm 2 It may be the following.
[0023] In this disclosure, the compressive load of graphite particles is a density of 1.7 g / cm 3 The larger the compression load, the less likely the graphite particles are to be deformed or broken by pressure. Specifically, a predetermined mass (e.g., 3.0 g) of graphite particles is filled into a die and compressed at a constant speed (e.g., 10 mm / min) until the density of the compressed graphite particles is 1.7 g / cm 3 Pressure (kN / cm 2 ) is the compression load of the graphite particle. In the above measurement, a die having a diameter of, for example, 15 mm is used, and compression is performed using an autograph (for example, manufactured by Shimadzu Corporation). The density of the graphite particles is measured based on the bottom area of the die (for example, 1.767 cm 2 ) and the volume of the graphite particles calculated from the distance from the bottom surface of the die to the pressing surface of the graphite particles, and the mass of the graphite particles.
[0024] (Springback rate) The springback ratio of the graphite particles is not particularly limited as long as the graphite particles can satisfy the above-mentioned formula (1). For example, from the viewpoint of further suppressing the breakage of the graphite particles due to pressing during the production of the negative electrode, the springback ratio of the graphite particles is preferably 0.25 or more, more preferably 0.27 or more, and more preferably 0.30 or more.
[0025] From the viewpoint of ease of densification by pressing during production of the negative electrode, the spring back ratio of the graphite particles may be 0.50 or less, 0.45 or less, or 0.40 or less.
[0026] In the present disclosure, the springback rate of graphite particles refers to the degree to which the density of graphite particles decreases when the graphite particles are compressed to a reference density and then pressure is released. The larger the springback rate, the easier it is for graphite particles deformed by compression to return to their original state. Specifically, a mold is filled with a predetermined mass (e.g., 3.0 g) of graphite particles, and the density of the graphite particles is determined to be equal to the reference density (e.g., 1.7 g / cm 3 The material is compressed at a constant speed (e.g., 10 mm / min) until it reaches a density (g / cm 2 ). The pressure is then released, and when the pressing surface stops moving due to elasticity, the density (g / cm 2 ) after pressure release is calculated. 3 ) is measured. The springback rate is calculated from the obtained value using the following formula. Springback rate = {(reference density - density after pressure release) / reference density} In the above measurement, a die having a diameter of, for example, 15 mm is used, and compression is performed using an autograph (for example, manufactured by Shimadzu Corporation). The density of the graphite particles is measured based on the bottom area of the die (for example, 1.767 cm 2 ) and the volume of the graphite particles calculated from the distance from the bottom surface of the die to the pressing surface of the graphite particles, and the mass of the graphite particles.
[0027] The compression load and springback rate of the graphite particles can be adjusted by changing the physical properties, composition, etc. of the raw material of the graphite particles (e.g., needle coke) or by changing the graphitization conditions, etc.
[0028] In the present disclosure, from the viewpoint of achieving superior cycle characteristics of a lithium ion secondary battery, the graphite particles may satisfy the following formula (2). [Springback rate x 7.6] + [Compressive load (kN / cm 2 )]≧4.5 (2)
[0029] In this disclosure, the average interplanar spacing (d 002 ) is less than 0.340 nm is considered to be graphite. In the present disclosure, as described below, graphite particles having low crystalline carbon disposed on at least a portion of the surface thereof are also referred to as "graphite particles". The average interplanar spacing of graphite crystals (d 002 ) is theoretically 0.3354 nm, and the closer it is to this value, the more graphitized it is. From the viewpoint of the initial charge / discharge efficiency and energy density of lithium-ion secondary batteries, the average interplanar spacing (d 002 ) is preferably 0.33600 nm or less, more preferably 0.33596 nm or less, and even more preferably 0.33592 nm or less. From the above viewpoint, the average interplanar spacing of graphite particles (d 002 ) is preferably 0.3354 nm to 0.33600 nm, more preferably 0.3354 nm to 0.33596 nm, and even more preferably 0.3354 nm to 0.33592 nm.
[0030] The average interplanar spacing of graphite particles (d 002 The average interplanar spacing (d) can be calculated using the Bragg equation based on the diffraction peak corresponding to the carbon 002 plane, which appears at a diffraction angle 2θ of approximately 24° to 27° in the diffraction profile obtained by irradiating a sample with X-rays (CuKα rays) and measuring the diffracted rays with a goniometer. 002 ) can be measured under the following conditions: Radiation source: CuKα ray (wavelength=0.15418nm) Output: 40kV, 20mA Sampling width: 0.010° Scanning range: 10°~35° Scan speed: 0.5° / min
[0031] Bragg's equation: 2dsinθ=nλ Here, d is the length of one period, θ is the diffraction angle, n is the reflection order, and λ is the X-ray wavelength.
[0032] (specific surface area) The specific surface area of the graphite particles is not particularly limited. For example, from the viewpoint of further suppressing the decomposition of the electrolyte, the specific surface area of the graphite particles is 2.7 m 2 / g or less, and 2.5m 2 / g or less is more preferable, and 2.2m 2 It is more preferable that the molecular weight is not more than 1 / g. The specific surface area of a graphite particle is 0.5 m 2 / g or more, and 2 / g or more, and 2 / g or more. 2 / g or more, the current density per unit area does not increase abruptly and the load is suppressed, so that rapid charge / discharge performance tends to be improved.
[0033] In this disclosure, the specific surface area of the graphite particles means the specific surface area determined by nitrogen adsorption measurement at 77K (N2 specific surface area). The N2 specific surface area can be determined by the BET method from an adsorption isotherm obtained by nitrogen adsorption measurement at 77 K. Specifically, the specific surface area can be determined by the method described in the Examples.
[0034] The specific surface area of the graphite particles can be adjusted by the particle size distribution, particle structure, and the like. The specific surface area of the graphite particles may be adjusted by coating the graphite particles. When it is desired to reduce the particle size, the specific surface area increases significantly due to the unevenness caused by grinding, but by coating the graphite particles, the unevenness is filled with a coating material to make it smooth and adjust the specific surface area.
[0035] (Graphite particle structure) The graphite particles may include a state in which a plurality of graphite particles are aggregated or bonded together (composite particles), and may also include composite particles having a structure in which a plurality of flat graphite particles are stacked (hereinafter also referred to as specific composite particles). The specific composite particles can reduce the contact area with the electrolyte inside the particles, compared to composite particles having a structure in which the main surfaces of multiple flat graphite particles are randomly oriented, and it is believed that the decomposition of the electrolyte can be effectively suppressed. In addition, it is believed that the particles are less likely to be deformed or broken even when pressure is applied when preparing the negative electrode, and the electrolyte path between the particles is easily secured. In addition, the electrolyte located inside the composite particles having a structure in which the main surfaces of multiple flat graphite particles are randomly oriented has a complex and slow migration and diffusion path. For this reason, it is believed that even an active material having a larger number of particle interfaces cannot exhibit high input / output performance due to diffusion obstacles. This tendency is particularly noticeable under input / output conditions with a high C rate.
[0036] The flat graphite particles contained in the specific composite particles refer to non-spherical graphite particles having anisotropic shape. Examples of the flat graphite particles include graphite particles having a scaly, flake, partially blocky, or other shape. The composite particles refer to particles in which primary particles are aggregated or bonded together. That is, the specific composite particles have a structure in which a plurality of flat graphite particles are stacked and aggregated or bonded together with their main surfaces facing each other. Therefore, a plurality of flat graphite particles are stacked in a substantially parallel state to form a composite particle. Whether or not the flat graphite particles are stacked can be confirmed by observation with a microscope.
[0037] The state in which a plurality of flaky graphite particles are aggregated or bonded refers to a state in which two or more flaky graphite particles are aggregated or bonded. Bonding refers to a state in which the particles are chemically bonded to each other directly or via a carbon substance. Aggregation refers to a state in which the particles are not chemically bonded to each other but maintain the shape of an aggregate due to their shape, etc. The flat graphite particles may be aggregated or bonded via a carbon substance. Examples of the carbon substance include graphite obtained by graphitizing an organic binder such as tar or pitch. Whether the flat graphite particles are aggregated or bonded can be confirmed, for example, by observation using a scanning electron microscope.
[0038] The flat graphite particles and the raw material thereof are not particularly limited, and examples thereof include artificial graphite, scaly natural graphite, scaly natural graphite, coke, resin, etc. Among them, artificial graphite is preferred from the viewpoint of being difficult to deform and having a low specific surface area. When natural graphite is used as a part of the raw material, the proportion of natural graphite in the specific composite particles is preferably 40 mass% or less from the viewpoint of being difficult to spheroidize and being easy to obtain a laminated structure.
[0039] The average particle size of the flat graphite particles constituting the specific composite particles is, for example, preferably 5 μm to 25 μm, more preferably 8 μm to 20 μm, and even more preferably 10 μm to 15 μm, from the viewpoint of ease of aggregation or bonding. The average particle size of the flat graphite particles can be determined by any of the following methods. The average particle size of the flat graphitizable aggregate described below that serves as the raw material for the specific composite particles, i.e., the particle size (D50) at which the cumulative total from the small diameter side in the volume-based particle size distribution is 50%, can be regarded as the average particle size of the flat graphite particles that make up the specific composite particles. The average particle size of the flaky graphite particles may be determined by observing the cross section of the specific composite particle with a scanning microscope and calculating the median particle size of 100 random flaky graphite particles. In this case, the particle size of each flaky graphite particle is defined as the equivalent circle diameter, which is the diameter of a circle having the same area as the projected area.
[0040] The particle size distribution D90 / D10 of the flaky graphite particles contained in the specific composite particles is preferably 4.4 or less, more preferably 4.0 or less, and even more preferably 3.5 or less. When the particle size distribution D90 / D10 of the plurality of flaky graphite particles is 4.4 or less, the particle size of the flaky graphite particles is relatively uniform, so that the contact area with the electrolyte inside the obtained specific composite particle can be further reduced, and decomposition of the electrolyte can be further suppressed. In addition, even if pressure is applied when preparing the negative electrode, deformation or destruction of the particles is less likely to occur, and paths for the electrolyte between the particles are more likely to be secured. The lower limit of the particle size distribution D90 / D10 of the plurality of flaky graphite particles is not particularly limited, but may be, for example, 2.0 or more.
[0041] The particle size distribution D90 / D10 of the flaky graphite particles can be determined by any of the following methods. The particle size distribution D90 / D10 obtained by measuring the flat graphitizable aggregate described below, which is the raw material for the specific composite particles, using a laser diffraction particle size distribution measuring device (e.g., SALD3100, Shimadzu Corporation) can be regarded as the particle size distribution D90 / D10 of the flat graphite particles that make up the specific composite particles. The particle size distribution D90 / D10 of the flat graphite particles can be determined by observing the cross section of the specific composite particle with a scanning microscope, and calculating the ratio of the particle size (D90) when the cumulative number of particles from the small diameter side of any 1,000 flat graphite particles is 90% to the particle size (D10) when the cumulative number of particles from the small diameter side is 10%. In this case, the particle size of each flat graphite particle is the equivalent circle diameter, which is the diameter of a circle having the same area as the projected area.
[0042] The aspect ratio of the flat graphite particles, expressed as A / B, where A is the length in the long axis direction and B is the length in the short axis direction, is preferably 2 to 20, and more preferably 4 to 10. When the aspect ratio is 2 or more, the outer surface area increases, which reduces the buoyancy and the particles tend to aggregate. When the particles aggregate, the surfaces having the long axis are stacked together so that the outer surface area is reduced, and the adhesion area between the particles is maximized, and the van der Waals force acting between the particles is also added, so that the particles tend to be more strongly adhered to each other and stabilized. When the aspect ratio is 20 or less, the input / output characteristics such as the rapid charge / discharge characteristics of the lithium ion secondary battery tend to be improved. In addition, when the aspect ratio is 20 or less, each flat graphite particle becomes thinner, the number of layers increases, the gaps in the particles increase, and the specific surface area increases, which tends to suppress the deterioration of the storage characteristics.
[0043] The aspect ratio is obtained by observing a graphite particle under a microscope, randomly selecting 100 graphite particles, measuring the A / B of each, and taking the arithmetic average of the measured values. In observing the aspect ratio, the length A in the long axis direction and the length B in the short axis direction are measured as follows. That is, in a projected image of a graphite particle observed under a microscope, two parallel tangents circumscribing the periphery of the graphite particle, tangents a1 and a2 whose distance is the maximum, are selected, and the distance between these tangents a1 and a2 is defined as the length A in the long axis direction. In addition, two parallel tangents circumscribing the periphery of the graphite particle, tangents b1 and b2 whose distance is the minimum, are selected, and the distance between these tangents b1 and b2 is defined as the length B in the short axis direction.
[0044] When the graphite particles contain specific composite particles, all of the graphite particles may be specific composite particles, or a portion of the graphite particles may be graphite particles other than the specific composite particles.
[0045] When the graphite particles are a mixture of specific composite particles and particles other than the specific composite particles, the ratio of the specific composite particles to the total amount of graphite particles may be 50% by mass or more, 60% by mass or more, 70% by mass or more, 80% by mass or more, or 90% by mass or more. Also, the ratio of the specific composite particles to the total amount of graphite particles may be 95% by mass or less.
[0046] The graphite particles may have low-crystalline carbon disposed on at least a portion of the surface thereof. When low-crystalline carbon is disposed on at least a portion of the surface of the graphite particles, the low-crystalline carbon tends to improve the charging characteristics at low temperatures when used in a lithium ion secondary battery. On the other hand, the graphite particles may not have low-crystalline carbon disposed on the surface. If low-crystalline carbon is not disposed on the surface of the graphite particles, cracks, peeling, etc., tend to occur in the graphite particles during pressing during electrode production, which increases the decomposition activity of the electrolyte and tends to suppress deterioration of storage characteristics. This also has the advantage of increasing the degree of freedom in manufacturing conditions. It has been found that the graphite particles of the present disclosure tend to have excellent rapid input / output characteristics even when low-crystalline carbon is not disposed on the surface. This is thought to be because the hardness, elasticity, etc. of the particles have a greater effect on the rapid input / output characteristics than the surface structure of the graphite particles.
[0047] In this disclosure, "low crystalline carbon" refers to carbon having an R value of 0.2 or more in a Raman spectrum. The R value in the Raman spectrum is 1360 cm in laser Raman spectroscopy with an excitation wavelength of 532 nm. -1 The intensity of the maximum peak appearing near Id and 1580 cm -1 When the intensity of the maximum peak that appears in the vicinity is Ig, the value is given as the intensity ratio Id / Ig of both peaks. 1360cm -1 The peaks appearing around 1300 cm are usually identified as corresponding to the amorphous structure of carbon, e.g., -1 ~1400cm -1 Also, the peak observed at 1580 cm -1 The peaks appearing around 1530 cm are usually identified as corresponding to the graphite crystal structure, e.g., -1 ~1630cm -1 This refers to the peak observed at
[0048] The R value is measured using a Raman spectrum measuring device (for example, XploRA PLUS by Horiba, Ltd.), and the spectrum obtained is measured under the following conditions with the following range as the baseline. Laser wavelength: 532nm Laser power: 100mW or more Neutral density filter: 1% ·Irradiation intensity: 1mW Measurement range: 1000cm -1 ~1800cm -1 - Irradiation time: 30 seconds ·Irradiation area: 1μm 2 Baseline (D band): 1100cm -1 ~1470cm -1 Baseline (G band): 1450cm -1 ~1710cm -1 Number of integrations per particle: 2 Number of particles measured: 30 particles
[0049] (Average particle size) From the viewpoint of further improving the permeability of the electrolyte, the average particle size of the graphite particles is, for example, preferably 5 μm to 30 μm, more preferably 8 μm to 25 μm, and further preferably 10 μm to 20 μm.
[0050] The average particle size of the graphite particles can be measured by a laser diffraction particle size distribution analyzer (e.g., SALD3100, Shimadzu Corporation). The average particle size is the particle size (D50) when the cumulative total from the small diameter side in the volume-based particle size distribution is 50%.
[0051] Methods for measuring the average particle size of graphite particles contained in a negative electrode include a method in which a sample electrode is prepared, embedded in an epoxy resin, mirror-polished, and the electrode cross section is observed with a scanning electron microscope (e.g., Keyence Corporation, "VE-7800"), and a method in which an electrode cross section is prepared using an ion milling device (e.g., Hitachi High-Technologies Corporation, "E-3500") and measured with a scanning electron microscope (e.g., Keyence Corporation, "VE-7800"). In this case, the average particle size is the median value of the particle sizes of 100 arbitrarily selected particles.
[0052] (Particle size distribution D90 / D10) The particle size distribution D90 / D10 of the graphite particles is preferably 5.0 or less, more preferably 4.0 or less, and even more preferably 3.0 or less. When the particle size distribution D90 / D10 of the graphite particles is 5.0 or less, it is believed that the path of the electrolyte is easily maintained well, and the injectability of the electrolyte is maintained well. The lower limit of the particle size distribution D90 / D10 of the graphite particles is not particularly limited, and may be, for example, 2.0 or more.
[0053] The particle size distribution D90 / D10 can be measured by a laser diffraction particle size distribution measuring device (for example, SALD3100, Shimadzu Corporation).
[0054] Methods for measuring the particle size distribution D90 / D10 of graphite particles contained in a negative electrode include a method in which a sample electrode is prepared, embedded in an epoxy resin, mirror-polished, and the electrode cross section is observed with a scanning electron microscope (e.g., Keyence Corporation, "VE-7800"), and a method in which an electrode cross section is prepared using an ion milling device (e.g., Hitachi High-Technologies Corporation, "E-3500") and measured with a scanning electron microscope (e.g., Keyence Corporation, "VE-7800"). In this case, the particle size distribution D90 / D10 can be determined by the following method. (1) Using a binarization method or the like, the area Sn (n is a particle unique number assigned to the selected particle) of the projected particle is calculated. (2) Assuming that the particle is an ideal sphere, calculate the equivalent circle diameter Ln = √Sn / π from the area Sn. (3) From the circle-equivalent diameter Ln, the sphere volume Vn = (4 / 3)π(Ln) 3 Request. (4) Repeat (1) to (3) for the 100 selected particles. (5) D90 / D10 can be calculated by taking the particle size at the point where the distribution curve, with the vertical axis representing the cumulative percentage of the volume of 100 particles and the horizontal axis representing particle size, intersects with the 10% axis as the 10% diameter (D10) and the 90% diameter (D90) as the point where it intersects with the 90% axis.
[0055] (Standard deviation of particle size distribution) The standard deviation of the particle size distribution of the graphite particles is preferably 0.30 or less, more preferably 0.25 or less, and even more preferably 0.20 or less. When the standard deviation of the particle size distribution is 0.30 or less, it is believed that the electrolyte path is easily maintained well, and the electrolyte pourability is maintained well. The lower limit of the standard deviation of the particle size distribution is not particularly limited. The standard deviation of the particle size distribution can be measured using a laser diffraction particle size distribution measuring device (e.g., SALD3100, Shimadzu Corporation) based on a frequency distribution graph with the horizontal axis being the logarithmic scale of particle size and the vertical axis being the particle amount (%).
[0056] (Oil absorption amount) The graphite particles may have an oil absorption of 10 mL / 100 g to 60 mL / 100 g, 15 mL / 100 g to 45 mL / 100 g, or 20 mL / 100 g to 40 mL / 100 g.
[0057] The oil absorption of graphite particles is an indicator of the amount of pores present inside and on the surface of the particles, and the amount of voids between the particles. When the oil absorption of graphite particles is 60 mL / 100 g or less, the number of pores present inside and on the particle surface is small, and the contact area with the electrolyte is considered to be sufficiently small. In addition, since the interface is small, it is possible to reduce the amount of binder used when preparing the negative electrode, which tends to reduce electrical resistance and improve battery performance. Furthermore, since there are few pores, it is possible to reduce the amount of solvent used when drying the electrode, which is advantageous in terms of cost and environment of the manufacturing line, such as reducing the equipment and power required for drying. When the oil absorption of the graphite particles is 10 mL / 100 g or more, the increase in viscosity of the slurry when kneaded with a binder, etc., which occurs when the voids between the particles are too small, tends to be suppressed. In addition, the binder tends to spread favorably and kneading tends to be easy. In addition, it is easy to secure voids between the particles for the movement of lithium ions.
[0058] In the present disclosure, the oil absorption of graphite particles is measured in the method described in JIS K6217-4:2017 “Carbon black for rubber use - Fundamental properties - Part 4: Determination of oil absorption” using linseed oil (for example, manufactured by Kanto Chemical Co., Ltd.) as the reagent liquid instead of dibutyl phthalate (DBP). Specifically, linseed oil is titrated into the target powder using a constant speed burette, and the change in viscosity characteristics is measured using a torque detector. The amount of linseed oil added per unit mass of the target powder that corresponds to 70% of the maximum torque generated is defined as the oil absorption (mL / 100g). As a measuring device, for example, an absorption measuring device (product name: S-500) manufactured by Asahi Research Institute Co., Ltd. can be used.
[0059] (Rhombohedral structure peak intensity ratio) In the X-ray diffraction pattern of the graphite particles using CuKα radiation, the intensity ratio of the diffraction peak (P1) of the (101) plane of the rhombohedral crystal structure to the diffraction peak (P2) of the (101) plane of the hexagonal crystal structure (P1 / P2, also called the rhombohedral crystal structure peak intensity ratio) may be 0.15 or less, 0.10 or less, or 0.05 or less. The peak intensity ratio (P1 / P2) is preferably in a range that cannot be observed by the following method. When the rhombohedral structure peak intensity ratio of the graphite particles is 0.15 or less, the degree of graphitization of the graphite particles is high, and the charge / discharge capacity tends to be higher.
[0060] The rhombohedral structure peak intensity ratio of graphite particles can be calculated from the intensity ratio of the diffraction line of the rhombohedral structure (P1: diffraction angle 43.2°) to the diffraction line of the hexagonal structure (P2: diffraction angle 44.3°) in the X-ray diffraction pattern using CuKα radiation. Here, the diffraction angle is expressed as 2θ (θ is the Bragg angle), and the diffraction line of the (101) plane of the rhombohedral structure appears at a diffraction angle of 43.2°, and the diffraction line of the (101) plane of the hexagonal structure appears at a diffraction angle of 44.3°.
[0061] (Graphitization degree) The degree of graphitization of the graphite particles as determined by X-ray diffraction may be 90.0% to 100.0%, 90.5% to 99.0%, or 91.0% to 98.0%. For example, when the degree of graphitization of relatively large graphite particles exceeding 12 μm is 98.0% or less, the graphite particles have a sufficiently high hardness and tend to be less susceptible to deformation, breakage, etc. When a high degree of graphitization is required, the hardness can also be increased by making the particle size smaller than 10 μm. For example, the particle shape can be maintained even with a degree of graphitization of 100%. When the graphite particles have a degree of graphitization of 90.0% or more, the discharge capacity tends to be excellent.
[0062] The degree of graphitization of the graphite particles can be determined, for example, as follows. 60 parts by mass of graphite particles and 40 parts by mass of silicon powder (e.g., Fujifilm Wako Pure Chemical Industries, purity 99.9%) are mixed in an agate mortar for 5 minutes, and the resulting mixture is placed in an X-ray diffraction measurement cell. Using an X-ray diffraction measurement device (e.g., Rigaku X-ray diffraction measurement device X-RAY DIFFRACTIOMETER MultiFlex), the diffraction angle corresponding to the graphite (002) plane and the diffraction angle corresponding to the silicon (111) plane are measured by X-ray diffraction measurement (2θ = 25° to 29°) using CuKα radiation. The correct diffraction angle of graphite is obtained by correcting the observed diffraction angles of silicon and graphite using the theoretical diffraction angle of Si (2θ = 28.442°). The interplanar spacing (Å) of the d(002) plane of the negative electrode material is calculated using Bragg's equation (2dsinθ=nλ), and the degree of graphitization is calculated using the following formula. Graphitization degree = [(3.44-planar spacing) / (0.086)] x 100
[0063] <Evaluation method for negative electrode materials for lithium-ion secondary batteries> The evaluation method of the negative electrode material for lithium ion secondary batteries disclosed herein is to evaluate the springback rate of graphite particles, which are the negative electrode material for lithium ion secondary batteries, and the compressive load (kN / cm 2The negative electrode material for lithium ion secondary batteries is evaluated using a regression equation obtained by multiple regression analysis using the above-mentioned properties as explanatory variables and the liquid absorption time of the negative electrode containing the negative electrode material for lithium ion secondary batteries as a response variable.
[0064] The present inventors have found that the combination of the springback rate and compressive load of the graphite particles, which are the negative electrode material, is strongly correlated with the liquid absorption. Therefore, by using the regression equation obtained by the multiple regression analysis as described above, the liquid absorption time of the negative electrode can be estimated from the springback rate and compressive load of the graphite particles. Since the cycle characteristics of a lithium ion secondary battery including the negative electrode can be evaluated from the liquid absorption time of the negative electrode, the performance of the negative electrode material for lithium ion secondary batteries can be easily evaluated by the evaluation method of the present disclosure.
[0065] For example, the liquid absorption time of a negative electrode using graphite particles having a specific springback rate and compression load can be estimated by the following regression equation (2). (Liquid absorption time) = ab × (Springback rate) - c × (Compressive load) (2) In formula (2), a, b, and c each represent a constant.
[0066] The number of samples of the springback rate, compression load, and liquid absorption time of the graphite particles when performing multiple regression analysis is not particularly limited as long as it is a normal number of samples when performing multiple regression analysis, and may be, for example, 20 or more, or 30 or more. In the above formula (2), the liquid absorption time may be a converted value when the value of the liquid absorption time of a specific sample is set to 100.
[0067] <Production method 1 for negative electrode material for lithium-ion secondary batteries> The manufacturing method 1 of the negative electrode material for lithium ion secondary batteries of the present disclosure manufactures the negative electrode material for lithium ion secondary batteries based on the evaluation results of the negative electrode material for lithium ion secondary batteries using the evaluation method of the negative electrode material for lithium ion secondary batteries of the present disclosure described above. The manufacturing method 1 of the present disclosure may include a step of graphitizing coke.
[0068] For example, in the manufacturing method 1 of the present disclosure, a negative electrode material for lithium ion secondary batteries may be manufactured, which is graphite particles having a springback rate and a compressive load such that the calculated value of the liquid absorption time is equal to or less than a specific value based on the relationship of the above formula (2). The preferred conditions for manufacturing a negative electrode material for lithium ion secondary batteries in the manufacturing method 1 of the present disclosure are the same as the conditions described in the manufacturing method 2 of the present disclosure below.
[0069] <Production method 2 for negative electrode material for lithium-ion secondary batteries> The method 2 for producing a negative electrode material for lithium ion secondary batteries according to the present disclosure is a method for producing a negative electrode material for lithium ion secondary batteries according to the present disclosure, and includes a step of graphitizing coke.
[0070] In the manufacturing method 2 of the present disclosure, coke is graphitized to manufacture a negative electrode material for lithium ion secondary batteries, which is artificial graphite. Graphite particles, which are artificial graphite, tend to have a higher springback ratio than natural graphite, and tend to more easily satisfy the above-mentioned formula (1).
[0071] The type of coke used in the above-mentioned production method 1 and production method 2 (hereinafter also simply referred to as the "production methods") is not particularly limited, and examples include petroleum-based or coal-based cokes such as fluid coke, needle coke, mosaic coke, and semi-needle coke having properties intermediate between needle coke and mosaic coke. Among these, needle coke and semi-needle coke, which tend to have a small thermal expansion coefficient, are preferably used. Furthermore, semi-needle coke and needle coke have high crystallinity, so flat particles are easily obtained. Furthermore, needle coke has high crystallinity, so the particles are large, and particle size adjustment is easy by crushing and classification. Only one type of coke may be used, or two or more types may be used in combination. Needle coke and semi-needle coke may be used in combination within a range that satisfies the above-mentioned conditions.
[0072] The method for obtaining the coke particles (coke particles) is not particularly limited and can be carried out by a known method. The particle size of the coke particles is not particularly limited and can be selected in consideration of the desired particle size, particle structure, etc. of the graphite particles.
[0073] In order to improve the compressive load of graphite particles, the thermal expansion coefficient of coke after firing at 1400°C is set to 2.30×10 -6 The thermal expansion coefficient of the coke after firing at 1400°C is preferably 2.50×10 -6 / ℃~4.00×10 -6 / °C, more preferably 2.80×10 -6 / ℃~3.70×10 -6 / °C. is even more preferred.
[0074] The thermal expansion coefficient of the coke is measured by the following method. 70g of coke calcined at 1400°C and 30g of binder pitch are mixed for 5 minutes to make a homogenized mixture. 15g of distilled oil, which is liquid at room temperature, is added to 100g of this mixture, and mixed for 3 minutes using a planetary mixer or the like to obtain a sample. This sample is placed in a pressure molding machine, and pressed at a surface pressure of 10MPa for 30 seconds to be molded. The molded product is heated from room temperature (25°C) to 1000°C in a nitrogen atmosphere over 5 hours, held at 1000°C for 1 hour, and then cooled to obtain a calcined product. This calcined product is cut into a size of 5.0mm x 5.0mm x 15.0mm using a precision cutting machine to obtain a test piece. The test piece is subjected to thermal expansion measurement in the measurement temperature range of 30°C to 500°C using a TMA (thermomechanical analyzer, for example, manufactured by Hitachi High-Technologies), and the CTE is calculated.
[0075] The graphite particles produced by the above-mentioned production method may be in a state in which a plurality of graphite particles are aggregated or bonded together (composite particles), or may be composite particles (specific composite particles) having a structure in which a plurality of flat graphite particles are stacked. Graphite particles in the form of specific composite particles can be produced, for example, by mixing flat coke particles with a binder, processing the resulting mixture to produce secondary particles having a structure in which flat coke particles are stacked, and then graphitizing the resulting secondary particles.
[0076] In a preferred embodiment, a method for producing a negative electrode material includes the steps of: mixing the flattened coke particles with a binder to obtain a mixture; A step of processing the mixture to produce secondary particles having a structure in which the flat coke particles are stacked; and a step of graphitizing the secondary particles to obtain composite particles (specific composite particles) having a structure in which a plurality of flat graphite particles are stacked.
[0077] In the case of producing the specific composite particles, the above method may include a step of classifying flat coke particles to remove at least one selected from the group consisting of fine particles and coarse particles. By classifying the coke particles, the layered structure of the specific composite particles is formed more densely, and the specific surface area tends to be further reduced.
[0078] When producing the specific composite particles, the above method may include a step of classifying the obtained specific composite particles to remove at least one selected from the group consisting of fine particles and coarse particles. By classifying the specific composite particles, the variation in particle size of the specific composite particles is suppressed, and the path of the electrolyte tends to be better maintained.
[0079] Therefore, in a preferred embodiment, the method for producing the negative electrode material includes the steps of: (a) optionally classifying the coke particles to remove at least one selected from the group consisting of fine particles and coarse particles; (b) mixing the flattened coke particles with a binder to obtain a mixture; (c) processing the mixture to produce secondary particles having a structure in which the flat coke particles are stacked; (d) graphitizing the secondary particles to obtain composite particles (specific composite particles) having a structure in which a plurality of flat graphite particles are stacked; (e) if necessary, classifying the composite particles to remove at least one selected from the group consisting of fine particles and coarse particles, in this order.
[0080] In this disclosure, "fine particles" refers to particles having a smaller particle size than the particles recovered by classification, and "coarse particles" refers to particles having a larger particle size than the particles recovered by classification.
[0081] Each step that may be included in the method for producing the negative electrode material of the present disclosure will be described in detail below.
[0082] [(a) A step of classifying flat coke particles to remove at least one selected from the group consisting of fine particles and coarse particles] The flat coke particles may be classified before being composited to remove at least one selected from the group consisting of fine particles and coarse particles. By classification, the particle size distribution D90 / D10 of the flat coke particles may be adjusted to, for example, 2.0 to 4.4, preferably 2.0 to 4.0, and more preferably 2.0 to 3.5.
[0083] In the classification, it is preferable to remove fine particles having a particle size of 1 μm or less, more preferable to remove fine particles having a particle size of 2 μm or less, and further preferable to remove fine particles having a particle size of 3 μm or less.
[0084] In the classification, it is preferable to remove coarse particles having a particle size of 60 μm or more, more preferable to remove coarse particles having a particle size of 50 μm or more, and even more preferable to remove coarse particles having a particle size of 40 μm or more. The removed coarse particles may be crushed and reused as a raw material.
[0085] The classification method is not particularly limited, and examples thereof include classification using a sieve, classification using an airflow centrifuge, a precision airflow classifier utilizing the Coanda effect, etc. In addition, the mixture can also be adjusted by applying a concentrated compressive pressure to coarse particles using a roll mill to pulverize them.
[0086] (b) Mixing the flat coke particles with a binder to obtain a mixture The binder used is a graphitizable binder, and examples of the binder include coal-based, petroleum-based, and artificial pitch and tar, thermoplastic resin, thermosetting resin, starch, etc. It is preferable to select a binder with low viscosity so that the flat particles have high fluidity in the mixing process. If necessary, a graphitization catalyst, a fluidity imparting agent, etc. may be added. Examples of the graphitization catalyst include substances having a graphitization catalytic action, such as silicon, iron, nickel, titanium, boron, vanadium, and aluminum, as well as carbides, oxides, and nitrides of these substances, and micaceous clay minerals.
[0087] The content of the graphitization catalyst is not limited as long as the target product can be obtained. From the viewpoint of not proceeding graphitization too much, it is preferable to not add the graphitization catalyst or to reduce the amount of the graphitization catalyst added. For example, when the graphitization catalyst is silicon carbide (SiC), the content of silicon carbide is preferably 5 mass% or less, more preferably 3 mass% or less, based on the mass of the graphitizable aggregate. More preferably, it is 1 mass% or less.
[0088] The mixing method is not particularly limited. From the viewpoint of reducing the amount of pores in the secondary particles, a mixing method that does not apply shear force as much as possible, for example, a mixing method using a kiln type mixer, a huddle stirrer, etc. is preferred. It is preferable not to use a kneader or the like that involves kneading, which is called a kneader.
[0089] [(c) Processing the mixture to produce secondary particles having a structure in which a plurality of flat coke particles are layered] The method of processing the mixture is not particularly limited. In one embodiment, the mixture may be processed by heating it to volatilize the volatile components of the binder. The heating temperature is preferably 400°C or less. When the heating temperature is 400°C or less, fine holes due to oxidative combustion are unlikely to be formed, and particles with a small specific surface area are likely to be obtained. At this time, the mixture is heated while being fluidized with a stirrer or the like, which makes it easier to granulate it.
[0090] When the mixture is heated, the pressure in the atmosphere may be reduced. By reducing the pressure in the atmosphere, the binder is more likely to be impregnated into the coke particles, the gaps in the particles are filled, and stacked particles with fewer internal pores are more likely to be obtained.
[0091] A specific example of a method for producing secondary particles will be described below. The mixture of coke particles and binder is stirred and mixed over a period of time at a temperature above the softening point of the binder, preferably in a temperature range where the volatile components volatilize, until the volatile components are removed. By slowly degassing before graphitization (firing), the generation of bubbles is reduced when the crystals are sintered, and the particles tend to have fewer pores inside and on the surface of the particles, which makes the structure hard, has a low specific surface area, and has excellent high temperature resistance. In this case, it is preferable to flow an inert gas such as nitrogen into the mixer to keep the oxygen concentration at 15% or less so that the volatile gas does not ignite, which is excellent in terms of safety. In addition, it is preferable that the temperature inside the mixer is 400°C or less, because it is difficult for fine holes to be formed due to oxidative combustion, and it is easy to obtain particles with a small specific surface area. In addition, when pitch is used as the binder, oxygen in the atmosphere can be taken into the pitch to make it infusible. This allows the crystals to develop well during graphitization, and a denser and higher crystal body can be obtained. However, since unevenness due to oxidation is likely to occur, it is required to adjust the temperature taking into consideration the specific surface area and hardness. When deaeration, infusibility and reduced pressure treatment are carried out in an environment where the fluidity of the liquid phase or gas phase in which the binder component is softened is ensured, greater effects tend to be obtained.
[0092] [(d) Graphitizing the secondary particles to obtain composite particles (specific composite particles) having a structure in which a plurality of flat graphite particles are stacked] In this step, the secondary particles obtained are graphitized. As a result, the graphitizable components in the secondary particles are graphitized. The graphitization is preferably performed in an atmosphere in which the mixture is unlikely to be oxidized, for example, a method of heating in a nitrogen atmosphere or argon gas can be mentioned. The temperature during graphitization is not particularly limited as long as it is a temperature at which the graphitizable components can be graphitized. For example, it may be 2000°C or higher, 2500°C or higher, 2800°C or higher, or 3000°C or higher. The upper limit of the temperature is not particularly limited as long as the graphite does not sublimate, and may be, for example, 3200°C or lower. When the temperature is 2000°C or higher, a change in crystal occurs. When the temperature is 2500°C or higher, the graphite crystals develop well, and when it is 2800°C or higher, it develops into high-capacity graphite crystals that can occlude more lithium ions, and the amount of graphitization catalyst remaining after firing is small, and the increase in the ash content tends to be suppressed. In either case, the charge / discharge capacity and the cycle characteristics of the battery tend to be good. On the other hand, when the graphitization temperature is 3200° C. or lower, sublimation of a portion of the graphite can be suppressed.
[0093] The method for producing the negative electrode material may include a step of forming the secondary particles into a shape such as a block before graphitization, and a step of crushing the formed body after graphitization. By forming the secondary particles, the bulk density increases, so the loading capacity of the graphitization furnace increases, and energy efficiency increases, allowing graphitization with less energy. Furthermore, when graphitizing a formed body formed from secondary particles into a shape such as a block, the compression load of the graphite particles tends to be improved compared to when the secondary particles are packed into a case or the like and the powder-like secondary particles are graphitized. In particular, from the viewpoint of further improving the compression load of graphite, it is preferable to use a graphite having a thermal expansion coefficient of 2.80×10 after sintering at 1400° C. -6 It is preferable to use coke having a temperature of 100 / ° C. or higher as a raw material, and form secondary particles into a shape such as a block, and graphitize the formed product. In addition, when graphitizing a molded product obtained by molding the secondary particles into a shape such as a block, graphite with high crystallinity is easily obtained, and the discharge capacity of the lithium ion secondary battery tends to be excellent, compared to when the secondary particles are packed into a case or the like and the powder-like secondary particles are graphitized. The molding method is not particularly limited, and for example, the secondary particles may be placed in a container such as a mold and pressurized. It is also preferable that the method for producing the negative electrode material does not include a step of forming the secondary particles before graphitization (and therefore does not include a step of pulverizing the formed body), which is believed to suppress an increase in rhombohedral crystals during the forming and pulverization processes and more suitably improve high temperature resistance.
[0094] The bulk density of the secondary particles before graphitization is 0.4 g / cm 3 ~1.2g / cm 3 and preferably 0.6 g / cm 3 ~1.1g / cm 3 More preferably, it is 0.8 g / cm 3 ~1.0g / cm 3 It is more preferable that the bulk density of the secondary particles before graphitization is 0.4 g / cm 3 If the bulk density of the secondary particles before graphitization is 1.0 g / cm or more, the number of voids in the particles is relatively small, so that it is possible to obtain high-density composite particles even after graphitization. 3 If the amount is equal to or less than this, crushing after graphitization becomes unnecessary or crushing can be performed with a weak force, and an increase in rhombohedral crystals tends to be suppressed.
[0095] In the present disclosure, the bulk density of the particles can be determined by a gravimetric method. That is, the bulk density of the particles can be determined by dividing the mass of the particles in air by the bulk volume. Here, the mass of the particles is the mass excluding the graphitization catalyst (for example, when the secondary particles are mixed particles of an aggregate, a binder, and a graphitization catalyst, the total mass excluding the volatile components of the aggregate and the binder).
[0096] [(e) Step of classifying the composite particles to remove at least one selected from the group consisting of fine particles and coarse particles] The obtained composite particles may be classified to remove at least one selected from the group consisting of fine particles and coarse particles. This may allow the particle size of the composite particles to be uniform, and the electrolyte passage may be more favorably maintained. By classification, the particle size distribution D90 / D10 of the composite particles may be adjusted to the above-mentioned range, for example, 2.0 to 5.0, preferably 2.0 to 4.0, and more preferably 2.0 to 3.0.
[0097] The classification method is not particularly limited, and examples thereof include classification using a sieve, classification using an airflow centrifuge, precision airflow classifier utilizing the Coanda effect, etc. The mixture can also be adjusted by applying a concentrated compressive pressure to coarse particles using a roll mill to pulverize them.
[0098] When removing fine particles in this step, it is preferable to remove fine particles having a particle size of, for example, 1 μm or less, more preferably to remove fine particles having a particle size of 2 μm or less, and even more preferably to remove fine particles having a particle size of 3 μm or less. When removing coarse particles in this step, it is preferable to remove coarse particles having a particle size of, for example, 60 μm or more, more preferably 50 μm or more, and even more preferably 40 μm or more.
[0099] [Other steps] The method for producing the negative electrode material of the present disclosure may include steps other than the steps described above. For example, the method for producing the negative electrode material may include a step of attaching an organic compound to the surface of the secondary particles after graphitization and performing a heat treatment. By attaching an organic compound to the surface of the secondary particles and performing a heat treatment, the organic compound attached to the surface is converted into low-crystalline carbon. This allows low-crystalline carbon to be arranged on at least a part of the surface of the composite particle.
[0100] The method of attaching an organic compound to the surface of the secondary particles is not particularly limited. For example, a wet method in which the secondary particles are dispersed and mixed in a mixed solution in which an organic compound is dissolved or dispersed in a solvent, and then the solvent is removed to attach the secondary particles; a dry method in which mechanical energy is applied to a mixture obtained by mixing the secondary particles and a solid organic compound to attach the secondary particles; etc. can be mentioned.
[0101] The organic compound is not particularly limited as long as it is a compound that can be converted into low-crystalline carbon by heat treatment (carbon precursor). For example, petroleum pitch, naphthalene, anthracene, phenanthroline, coal tar, phenolic resin, polyvinyl alcohol, etc. The organic compound may be used alone or in combination of two or more kinds.
[0102] The heat treatment temperature when the secondary particles having an organic compound attached to their surfaces are heat treated is not particularly limited as long as the organic compound attached to the surfaces of the secondary particles is converted into low-crystalline carbon, and is preferably, for example, 400° C. to 1500° C. From the viewpoint of particularly enhancing high-temperature resistance, it is more preferably 1000° C. to 1500° C. The heat treatment is preferably carried out in an inert gas atmosphere, such as a nitrogen atmosphere.
[0103] <Negative electrode for lithium-ion secondary batteries> The negative electrode for lithium ion secondary batteries of the present disclosure includes a negative electrode material layer including the negative electrode material for lithium ion secondary batteries of the present disclosure, and a current collector. The negative electrode for lithium ion secondary batteries may include other components as necessary in addition to the negative electrode material layer including the negative electrode material for lithium ion secondary batteries of the present disclosure and the current collector.
[0104] The negative electrode for lithium ion secondary batteries can be produced, for example, by kneading a negative electrode material for lithium ion secondary batteries and a binder together with a solvent to prepare a slurry-like negative electrode material composition for lithium ion secondary batteries, which is then applied onto a current collector to form a negative electrode material layer, or by forming the negative electrode material composition for lithium ion secondary batteries into a shape such as a sheet or pellet, and integrating this with a current collector. Kneading can be performed using a dispersing device such as a dispersing mixer or a planetary kneader.
[0105] The binder used in the preparation of the negative electrode material composition for lithium ion secondary batteries is not particularly limited. Examples of the binder include styrene-butadiene copolymer (SBR), ethylenically unsaturated carboxylic acid esters such as methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, butyl acrylate, butyl methacrylate, hydroxyethyl acrylate, and hydroxyethyl methacrylate, and homopolymers or copolymers of ethylenically unsaturated carboxylic acids such as acrylic acid, methacrylic acid, itaconic acid, fumaric acid, and maleic acid, and polymer compounds with high ion conductivity such as polyvinylidene fluoride, polyethylene oxide, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, and polymethacrylonitrile. When the negative electrode material composition for lithium ion secondary batteries contains a binder, the content of the binder is not particularly limited. For example, it may be 0.5 parts by mass to 20 parts by mass with respect to 100 parts by mass of the total of the negative electrode material for lithium ion secondary batteries and the binder.
[0106] The negative electrode material composition for lithium ion secondary batteries may contain a thickener. Examples of the thickener that can be used include carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, polyacrylic acid or a salt thereof, oxidized starch, phosphorylated starch, and casein. When the negative electrode material composition for lithium ion secondary batteries contains a thickener, the content of the thickener is not particularly limited. For example, the content may be 0.1 to 5 parts by mass with respect to 100 parts by mass of the negative electrode material for lithium ion secondary batteries.
[0107] The negative electrode material composition for lithium ion secondary batteries may contain a conductive auxiliary material. Examples of the conductive auxiliary material include carbon materials such as carbon black, graphite, and acetylene black, and inorganic compounds such as oxides and nitrides that exhibit electrical conductivity. When the negative electrode material composition for lithium ion secondary batteries contains a conductive auxiliary material, the content of the conductive auxiliary material is not particularly limited. For example, the content may be 0.5 parts by mass to 15 parts by mass with respect to 100 parts by mass of the negative electrode material for lithium ion secondary batteries.
[0108] The material of the current collector is not particularly limited and can be selected from aluminum, copper, nickel, titanium, stainless steel, etc. The state of the current collector is not particularly limited and can be selected from foil, perforated foil, mesh, etc. In addition, porous materials such as porous metal (foamed metal), carbon paper, etc. can also be used as the current collector.
[0109] When the negative electrode material composition for lithium ion secondary batteries is applied to a current collector to form a negative electrode material layer, the method is not particularly limited, and known methods such as metal mask printing, electrostatic painting, dip coating, spray coating, roll coating, doctor blade, comma coating, gravure coating, and screen printing can be adopted. After the negative electrode material composition for lithium ion secondary batteries is applied to the current collector, the solvent contained in the negative electrode material composition for lithium ion secondary batteries is removed by drying. Drying can be performed using, for example, a hot air dryer, an infrared dryer, or a combination of these devices. If necessary, the negative electrode material layer may be subjected to a rolling treatment. The rolling treatment can be performed using a method such as a flat plate press or a calendar roll.
[0110] When the negative electrode material composition for lithium ion secondary batteries formed into a shape such as a sheet or pellet is integrated with a current collector to form a negative electrode material layer, the integration method is not particularly limited. For example, it can be performed by rolling, flat plate pressing, or a combination of these means. The pressure when integrating the negative electrode material composition for lithium ion secondary batteries with the current collector is preferably, for example, about 1 MPa to 200 MPa.
[0111] The negative electrode density of the negative electrode layer is not particularly limited and is, for example, 1.1 g / cm 3 ~1.8g / cm 3 and preferably 1.1 g / cm 3 ~1.7g / cm 3 More preferably, it is 1.1 g / cm 3 ~1.6g / cm 3 It is more preferable that the negative electrode density is 1.1 g / cm 3By setting the capacitance at 1.8 g / cm or more, the increase in electrical resistance is suppressed and the capacitance tends to increase. 3 By setting the above range, deterioration of input characteristics and cycle characteristics tends to be suppressed.
[0112] <Lithium-ion secondary battery> The lithium ion secondary battery of the present disclosure includes the negative electrode for lithium ion secondary batteries of the present disclosure, a positive electrode, and an electrolyte solution.
[0113] The positive electrode can be obtained by forming a positive electrode layer on a current collector in the same manner as the negative electrode described above. The current collector can be made of a metal or alloy such as aluminum, titanium, or stainless steel in the form of a foil, a perforated foil, a mesh, or the like.
[0114] The positive electrode material used to form the positive electrode layer is not particularly limited. Examples of the positive electrode material include metal compounds (metal oxides, metal sulfides, etc.) that can dope or intercalate lithium ions, conductive polymer materials, etc. More specifically, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2), and composite oxides thereof (LiCo x Ni y Mn z O2, x+y+z=1), and a double oxide containing an additive element M' (LiCo a Ni b Mn c M' d O2, a+b+c+d=1, M': Al, Mg, Ti, Zr or Ge), spinel-type lithium manganese oxide (LiMn2O4), lithium vanadium compounds, V2O5, V6O 13 , VO2, MnO2, TiO2, MoV2O8, TiS2, V2S5, VS2, MoS2, MoS3, Cr3O8, Cr2O5, metal compounds such as olivine-type LiMPO4 (M: Co, Ni, Mn, Fe), conductive polymers such as polyacetylene, polyaniline, polypyrrole, polythiophene, polyacene, porous carbon, etc. The positive electrode material may be one type alone or two or more types.
[0115] The electrolytic solution is not particularly limited, and for example, a solution in which a lithium salt as an electrolyte is dissolved in a non-aqueous solvent (a so-called organic electrolytic solution) can be used. Examples of the lithium salt include LiClO4, LiPF6, LiAsF6, LiBF4, LiSO3CF3, etc. The lithium salt may be one type alone or two or more types. Examples of non-aqueous solvents include ethylene carbonate, fluoroethylene carbonate, chloroethylene carbonate, propylene carbonate, butylene carbonate, vinylene carbonate, cyclopentanone, cyclohexylbenzene, sulfolane, propane sultone, 3-methylsulfolane, 2,4-dimethylsulfolane, 3-methyl-1,3-oxazolidin-2-one, γ-butyrolactone, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, butyl methyl carbonate, ethyl propyl carbonate, butyl ethyl carbonate, dipropyl carbonate, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, methyl acetate, ethyl acetate, trimethyl phosphate, triethyl phosphate, etc. The non-aqueous solvent may be one type alone or two or more types.
[0116] The state of the positive electrode and the negative electrode in the lithium ion secondary battery is not particularly limited. For example, the positive electrode, the negative electrode, and a separator disposed between the positive electrode and the negative electrode as necessary may be wound in a spiral shape, or may be stacked in a flat plate shape.
[0117] The separator is not particularly limited, and for example, a resin nonwoven fabric, cloth, microporous film, or a combination thereof can be used. Examples of the resin include those mainly composed of polyolefins such as polyethylene and polypropylene. In the case where the positive electrode and the negative electrode are not in contact with each other due to the structure of the lithium ion secondary battery, a separator does not need to be used.
[0118] The shape of the lithium ion secondary battery is not particularly limited, and examples thereof include laminate type batteries, paper type batteries, button type batteries, coin type batteries, stacked type batteries, cylindrical batteries, and square batteries.
[0119] In particular, conventional cylindrical batteries are used in electric vehicles (EVs) and the like, and the negative electrode material layer is densified and packed into a cylindrical case, so there is a tendency to significantly suppress the decrease in cycle capacity retention caused by the disconnection between graphite particles, which is a concern when repeatedly charging and discharging. However, because the negative electrode material layer is densified, the gaps between the graphite particles disappear during repeated charging and discharging, resulting in areas where the electrolyte and the negative electrode active material cannot come into contact, which results in an issue of a decrease in cycle capacity retention due to increased cell resistance.
[0120] On the other hand, the lithium ion secondary battery of the present disclosure uses a negative electrode material capable of producing a negative electrode with excellent liquid absorption. Therefore, even when the negative electrode material layer is densified like a cylindrical battery, the lithium ion secondary battery of the present disclosure can suppress both the decrease in cycle capacity retention rate caused by disconnection between graphite particles and the decrease in cycle capacity retention rate caused by the occurrence of portions where the electrolyte and the negative electrode active material cannot contact each other, and tends to have excellent cycle characteristics.
[0121] The lithium ion secondary battery of the present disclosure is suitable as a large-capacity lithium ion secondary battery for use in electric vehicles, power tools, power storage devices, and the like. EXAMPLES
[0122] The present disclosure will be specifically described below with reference to examples, but the present disclosure is not limited to these examples.
[0123] <Determining the correlation between liquid absorption time and powder properties> Needle coke, a petroleum-derived coke, was used as the raw material for the graphite particles. The coke was crushed by a hammer mill. The crushed material was sieved using a sieve with 3 mm openings, and the under-sieve material was sieved using a sieve with 1 mm openings to collect granules with particle sizes of 1 mm to 3 mm.
[0124] The obtained coke particles were pulverized and classified using a roller mill (Kurimoto Iron Works, Ltd., K-VX mill) to obtain flat coke particles.
[0125] 90% by mass of the obtained coke particles and 10% by mass of coal tar pitch (softening point 100°C to 150°C, quinoline insoluble content 15% by mass or less, fixed carbon 55% to 75% by mass) were mixed at room temperature to obtain a mixture. Next, the inside of the mixing vessel containing the mixture was heated to 300°C to 400°C under a mixed gas flow of dry air and nitrogen, and the pressure was reduced. At this time, if the stirring blades in the mixer are moved to make it easier to discharge the gas, the specific surface area is likely to decrease. The end point of the heating and stirring is determined by utilizing the phenomenon in which low molecular weight gas in the coal tar pitch volatilizes and the viscosity of the mixture decreases, and is the point when the current value of the stirring blade decreases and stabilizes, and the bulk density reaches 0.7 g / cm. 3 secondary particles were obtained.
[0126] The secondary particles were then packed into a graphitization case and graphitized at 3100° C. The resulting particles were then sieved through a 300 mesh screen to obtain graphite particles.
[0127] In addition to the graphite particles mentioned above, 10 types of graphite particles were prepared by changing the conditions of crushing and classifying the coke particles, the stirring conditions of the mixer, the graphitization conditions, etc. Using these 10 types of graphite particles, D50, standard deviation of particle size distribution, specific surface area, tap density, compression load and springback rate were determined, and further, using these graphite particles, a negative electrode was manufactured as follows, and the orientation of the graphite particles in the negative electrode and the liquid absorption time of the negative electrode were determined.
[0128] (Tap density) Capacity 150cm 3A 100 cm sample of graphite powder was placed in a graduated flat-bottom test tube (KRS-406, manufactured by Kuramochi Scientific Instruments Manufacturing Co., Ltd.). 3 The graduated flat-bottomed test tube was then stopped up, and the graduated flat-bottomed test tube was then dropped 250 times from a height of 5 cm, after which the tap density was calculated from the mass and volume of the sample powder.
[0129] (Measurement of the orientation of graphite particles in the negative electrode) Graphite particles (97.6 parts by mass), carboxymethyl cellulose (CMC) (1.2 parts by mass), and styrene-butadiene rubber (SBR) (1.2 parts by mass) were mixed together to prepare a slurry. This slurry was applied to the shiny surface of the electrolytic copper foil at a coating amount of 10 g / cm. 2 After pre-drying at 90°C for 2 hours, the electrode density was adjusted to 1.70 g / cm using a roll press. 3 Thereafter, a curing treatment was carried out by drying at 120° C. for 4 hours in a vacuum atmosphere, thereby obtaining a negative electrode for a lithium ion secondary battery.
[0130] The orientation of graphite particles was determined by measuring the surface of the sample electrode, a negative electrode for a lithium-ion secondary battery, using an X-ray diffractometer with a CuKα X-ray source. Specifically, the X-ray diffraction pattern of the surface of the sample electrode was measured, and the orientation of the graphite particles was calculated from the intensities of the carbon (002) plane diffraction peak detected at a diffraction angle 2θ of approximately 20° to 20° and the carbon (110) plane diffraction peak detected at a diffraction angle 2θ of approximately 70° to 80°, using the following formula (X). (002) diffraction peak intensity / (110) diffraction peak intensity (X)
[0131] The physical properties other than the tap density and the orientation of the graphite particles in the negative electrode were determined by the methods described above.
[0132] (Measurement of liquid absorption time) The negative electrode for lithium ion secondary batteries obtained in the same manner as in (Measurement of the orientation of graphite particles in the negative electrode) was punched out into a square of 2.0 cm x 2.0 cm, and attached to a glass substrate with double-sided tape to obtain a flat electrode surface without distortion. 3 μL of PC (polycarbonate: manufactured by Kishida Chemical Co., Ltd.) was dropped onto the center of this square electrode using a micropipette, and the time it took for the liquid to penetrate was measured. Six identical electrodes were prepared, and the average time of six measurements was calculated. Next, manufacture under the above conditions and compressive load 2.804kN / cm 2 The value of the liquid absorption time in the negative electrode for lithium ion secondary batteries prepared using graphite particles having a spring back rate of 0.277 was defined as a reference value of 100, and the value of the liquid absorption time measured in each negative electrode for lithium ion secondary batteries was converted based on the above reference value to be used as the liquid absorption time index.
[0133] The correlation between the powder properties and the liquid absorption time index for 10 types of graphite particles was determined by simple regression analysis and multiple regression analysis. The results of the simple regression analysis are shown in Table 1, and the results of the multiple regression analysis are shown in Table 2.
[0134] [Table 1]
[0135] [Table 2]
[0136] As shown in Tables 1 and 2, the regression equation with the strongest correlation was obtained by performing multiple regression analysis with the springback rate and compression load as explanatory variables and the liquid absorption time index as the objective variable. The obtained regression equation is shown below. Regression equation: (Liquid absorption time index) = 337.7 - 369 x (Springback rate) - 48.4 x (Compression load)
[0137] When the value of the liquid absorption time index is about 135 or less, the liquid absorption of the lithium ion secondary battery is good, and the deterioration of the cycle characteristics during repeated charging and discharging tends to be suppressed. Therefore, we considered that the lithium ion cycle characteristics will be good when the right side of the above regression equation is 135 or less, and derived the following equation (1). [Springback rate x 7.6] + [Compressive load (kN / cm 2 )]≧4.2 (1)
[0138] Graphite particles were prepared in each of the following Examples and Comparative Examples, and the compression load and springback rate of the prepared graphite particles were measured. Then, the liquid absorption time index of the negative electrode obtained using the graphite particles prepared in each Example and Comparative Example was calculated based on the above regression equation, and the cycle capacity retention index was calculated from the calculated liquid absorption time index.
[0139] Example 1 Needle coke, a petroleum-derived coke, was used as the raw material for the graphite particles. The coke was crushed by a hammer mill. The crushed material was sieved using a sieve with 3 mm openings, and the under-sieve material was sieved using a sieve with 1 mm openings to collect granules with particle sizes of 1 mm to 3 mm.
[0140] The obtained coke particles were pulverized and classified using a roller mill (Kurimoto Iron Works, Ltd., K-VX mill) to obtain flat coke particles. The volumetric particle size distribution of the coke particles was measured, and D10 was 8.9 μm, D50 was 15.8 μm, and D90 was 23.5 μm. The thermal expansion coefficient of the coke particles after firing at 1400 °C was 3.52 × 10 -6 / ℃.
[0141] 85% by mass of the obtained coke particles and 15% by mass of coal tar pitch (softening point 100°C to 150°C, quinoline insoluble content 15% by mass or less, fixed carbon 55% by mass to 75% by mass) were mixed at room temperature to obtain a mixture. Next, the inside of the mixing vessel containing the mixture was heated to 300°C to 400°C under a mixed gas flow of dry air and nitrogen, and the pressure was reduced. At this time, if the stirring blade in the mixer is moved to make it easier to discharge the gas, the specific surface area is likely to decrease. The end point of the heating and stirring was determined by utilizing the phenomenon in which low molecular weight gas in the coal tar pitch volatilizes and the viscosity of the mixture decreases, and the current value of the stirring blade decreased and stabilized, and secondary particles were obtained.
[0142] The secondary particles were then packed into a graphitization case and graphitized at 3100° C. The resulting particles were then sieved through a 300 mesh screen to obtain graphite particles. The volumetric particle size distribution of the graphite particles was measured, and found to be D10 of 9.0 μm, D50 of 16.0 μm, and D90 of 24.9 μm. The compression load and springback rate of the obtained graphite particles were measured, and the results are shown in Table 3.
[0143] Example 2 Needle coke, which is a petroleum-derived coke different from that in Example 1, was used as the raw material for graphite particles. Flat coke particles were obtained in the same manner as in Example 1. The volumetric particle size distribution of the coke particles was measured, and D10 was 8.2 μm, D50 was 13.2 μm, and D90 was 20.8 μm. The thermal expansion coefficient of the coke particles after firing at 1400 °C was 3.57 × 10 -6 / ℃.
[0144] The obtained coke particles were used to prepare graphite particles in the same manner as in Example 1. The volumetric particle size distribution of the graphite particles was measured, and D10 was 8.5 μm, D50 was 14.6 μm, and D90 was 22.5 μm. The results of measuring the compression load and springback rate of the graphite particles are shown in Table 3.
[0145] Example 3 Secondary particles were obtained in the same manner as in Example 1 using the coke particles obtained in Example 2. The obtained secondary particles were then molded by uniaxial pressing at room temperature to obtain a block-shaped molded product. The obtained molded product was then heat-treated at 800°C to 850°C in a nitrogen atmosphere, and then graphitized at 2600°C to 3100°C to obtain a graphitized product. The obtained graphitized product was pulverized, and the obtained particles were sieved through a 300 mesh screen to obtain graphite particles. The volumetric particle size distribution of the graphite particles was measured, and found to be D10 of 9.5 μm, D50 of 17.5 μm, and D90 of 31.2 μm. The compression load and springback rate of the obtained graphite particles were measured, and the results are shown in Table 3.
[0146] Example 4 The coke particles obtained in Example 1 were used to obtain graphite particles in the same manner as in Example 3. The volumetric particle size distribution of the graphite particles was measured, and found to be D10 of 10.0 μm, D50 of 18.4 μm, and D90 of 33.1 μm. The compression load and springback rate of the obtained graphite particles were measured, and the results are shown in Table 3.
[0147] Example 5 Needle coke, which is a petroleum-derived coke different from that in Example 1, was used as the raw material for graphite particles. Flat coke particles were obtained in the same manner as in Example 1. The volumetric particle size distribution of the coke particles was measured, and D10 was 9.4 μm, D50 was 15.8 μm, and D90 was 21.4 μm. The thermal expansion coefficient of the coke particles after firing at 1400 °C was 3.90 × 10 -6 / ℃.
[0148] The obtained coke particles were used to prepare graphite particles in the same manner as in Example 1. The volumetric particle size distribution of the graphite particles was measured, and D10 was 9.6 μm, D50 was 16.1 μm, and D90 was 23.4 μm. The results of measuring the compression load and springback rate of the graphite particles are shown in Table 3.
[0149] Example 6 Needle coke, which is a petroleum-derived coke different from that in Example 1, was used as the raw material for graphite particles. Flat coke particles were obtained in the same manner as in Example 1. The volumetric particle size distribution of the coke particles was measured, and D10 was 6.4 μm, D50 was 12.5 μm, and D90 was 18.0 μm. The thermal expansion coefficient of the coke particles after firing at 1400 °C was 2.30 × 10 -6 / ℃.
[0150] The coke particles obtained in Example 6 were used to obtain graphite particles in the same manner as in Example 3. The volumetric particle size distribution of the graphite particles was measured, and found to be D10 of 11.4 μm, D50 of 19.2 μm, and D90 of 33.1 μm. The compression load and springback rate of the obtained graphite particles were measured, and the results are shown in Table 3.
[0151] Example 7 Needle coke, which is a petroleum-derived coke different from that in Example 1, was used as the raw material for graphite particles. Flat coke particles were obtained in the same manner as in Example 1. The volumetric particle size distribution of the coke particles was measured, and D10 was 7.3 μm, D50 was 13.9 μm, and D90 was 25.2 μm. The thermal expansion coefficient of the coke particles after firing at 1400 °C was 2.72 × 10 -6 / ℃.
[0152] The coke particles obtained in Example 7 were used to obtain graphite particles in the same manner as in Example 3. The volumetric particle size distribution of the graphite particles was measured, and found to be D10 of 8.8 μm, D50 of 18.8 μm, and D90 of 36.4 μm. The compression load and springback rate of the obtained graphite particles were measured, and the results are shown in Table 3.
[0153] Example 8 The same needle coke as in Example 7 was used as the raw material for graphite particles. Flat coke particles were obtained in the same manner as in Example 1. The volumetric particle size distribution of the coke particles was measured, and D10 was 3.3 μm, D50 was 10.4 μm, and D90 was 22.3 μm.
[0154] Graphite particles were obtained in the same manner as in Example 3, except that 81 mass% of the coke particles obtained in Example 8 was used as the raw material, and 9 mass% and 10 mass% of coal tar and starch (gelatinization degree 95% or more) were used as the binder. The volumetric particle size distribution of the graphite particles was measured, and D10 was 5.5 μm, D50 was 12.5 μm, and D90 was 21.4 μm. The results of measuring the compression load and springback rate of the obtained graphite particles are shown in Table 3.
[0155] Example 9 The same needle coke as in Example 7 was used as the raw material for graphite particles. Flat coke particles were obtained in the same manner as in Example 1. The volumetric particle size distribution of the coke particles was measured, and D10 was 5.1 μm, D50 was 10.1 μm, and D90 was 17.7 μm.
[0156] Graphite particles were obtained in the same manner as in Example 3, except that 90% by mass of the coke particles obtained in Example 9 was used as the raw material, and 10% by mass of starch (gelatinization degree 95% or more) was used as the binder. The volumetric particle size distribution of the graphite particles was measured, and D10 was 6.4 μm, D50 was 14.0 μm, and D90 was 29.6 μm. The results of measuring the compression load and springback rate of the obtained graphite particles are shown in Table 3.
[0157] Example 10 Needle coke, which is a petroleum-derived coke different from that in Example 1, was used as the raw material for graphite particles. Flat coke particles were obtained in the same manner as in Example 1. The volumetric particle size distribution of the coke particles was measured, and D10 was 8.8 μm, D50 was 13.9 μm, and D90 was 19.0 μm. The thermal expansion coefficient of the coke particles after firing at 1400 °C was 2.25 × 10 -6 / ℃.
[0158] A mixture was obtained by mixing 85 parts by mass of the coke particles and 15 parts by mass of coal tar pitch (softening point 100°C to 150°C, quinoline insoluble content 15% by mass or less, fixed carbon 55% by mass to 75% by mass) at room temperature. Next, graphite particles were obtained using the mixture obtained in the same manner as in Example 3. The volumetric particle size distribution of the graphite particles was measured, and D10 was 12.0 μm, D50 was 19.5 μm, and D90 was 28.6 μm. The compression load and springback rate of the obtained graphite particles were measured, and the results are shown in Table 3.
[0159] [Comparative Examples 1 to 3] Spherical natural graphite having a D10 of 15.1 μm, a D50 of 22.0 μm, and a D90 of 30.5 μm was used as the graphite particles of Comparative Example 1, spherical natural graphite having a D10 of 2.3 μm, a D50 of 4.0 μm, and a D90 of 6.3 μm was used as the graphite particles of Comparative Example 2, and spherical natural graphite having a D10 of 8.2 μm, a D50 of 10.5 μm, and a D90 of 13.6 μm was used as the graphite particles of Comparative Example 3. The compression load and springback rate of the graphite particles were measured by the above-mentioned method, and the results are shown in Table 3.
[0160] Comparative Example 4 Needle coke, which is a petroleum-derived coke different from that in Example 1, was used as the raw material for graphite particles. Flat coke particles were obtained in the same manner as in Example 1. The volumetric particle size distribution of the coke particles was measured, and D10 was 8.8 μm, D50 was 13.9 μm, and D90 was 19.0 μm. The thermal expansion coefficient of the coke particles after firing at 1400 °C was 2.25 × 10 -6 / ℃.
[0161] 85 parts by mass of coke particles, 15 parts by mass of coal tar pitch (softening point 100°C to 150°C, quinoline insoluble content 15% by mass or less, fixed carbon 55% by mass to 75% by mass), and 6 parts by mass of silicon carbide as a graphitization catalyst were mixed at room temperature to obtain a mixture. Next, graphite particles were obtained using the obtained mixture in the same manner as in Example 3. The volumetric particle size distribution of the graphite particles was measured, and found to be D10 of 11.4 μm, D50 of 19.7 μm, and D90 of 30.3 μm. The compression load and springback rate of the obtained graphite particles were measured, and the results are shown in Table 3.
[0162] Comparative Example 5 85 parts by mass of the coke particles obtained in Comparative Example 4, 15 parts by mass of coal tar pitch (softening point 100°C to 150°C, quinoline insoluble content 15% by mass or less, fixed carbon 55% by mass to 75% by mass), and 12 parts by mass of silicon carbide as a graphitization catalyst were mixed at room temperature to obtain a mixture. Next, graphite particles were obtained using the obtained mixture in the same manner as in Example 3. The volumetric particle size distribution of the graphite particles was measured, and found to be D10 of 11.0 μm, D50 of 19.9 μm, and D90 of 31.7 μm. The compression load and springback rate of the obtained graphite particles were measured, and the results are shown in Table 3.
[0163] (Compressive load) A 15 mm diameter die was filled with 3.0 g of anode material, which was then compressed at a constant speed of 10 mm / min using an Autograph (Shimadzu Corporation). During compression, the distance from the bottom of the anode material to the press surface was measured, and this was multiplied by the bottom area of the die to calculate the density of the anode material under pressure. A load cell was attached to the Autograph press hammer, and the density was measured at the specified density of 1.7 g / cm. 3 The applied pressure (kN / cm 2 ) was defined as the compression load.
[0164] (Springback rate) The standard density when pressed using the above method using an Autograph (Shimadzu Corporation) was 1.7 g / cm 3 The absolute value of the difference between the density of the negative electrode material after springback and the density of the negative electrode material after springback is 1.7 g / cm 3 The springback rate was calculated by dividing the
[0165] (Calculation of Absorption Time Index) The liquid absorption time index of the negative electrode was calculated using the compression load and springback rate of the graphite particles obtained in each Example and Comparative Example and the following regression equation. The results are shown in Table 3. Regression equation: (Liquid absorption time index) = 337.7 - 369 x (Springback rate) - 48.4 x (Compression load)
[0166] (Relationship between Absorption Time Index and Cycle Capacity Retention Rate)
[0167] <Production of lithium-ion secondary batteries> A coin cell was produced using the electrode obtained above as the negative electrode, metallic lithium as the counter electrode, a mixture of ethylene carbonate / ethyl methyl carbonate (3:7 volume ratio) containing 1M LiPF6 and vinylene carbonate (VC) (1.0 mass%) as the electrolyte, a 25 μm thick polyethylene microporous membrane as the separator, and a 250 μm thick copper plate as the spacer.
[0168] <Battery characteristic evaluation> The cycle characteristics of the lithium ion secondary battery prepared as described above were evaluated as follows. Specifically, the lithium-ion secondary battery thus fabricated was placed in a thermostatic chamber maintained at 25°C, and was charged at a constant current of 4.6 mA until the voltage reached 4.2 V, and then was further charged at a constant voltage of 4.2 V until the current attenuated to a value equivalent to 0.046 mA. After a 10-minute pause following charging, the battery was discharged at 4.6 mA until the voltage reached 2.75 V, and the initial discharge capacity was measured. This charging and discharging cycle was repeated for a further 299 cycles. At this time, the discharge capacity at the 100th cycle and the discharge capacity at the 300th cycle were measured. The discharge capacity after each cycle was divided by the initial discharge capacity, and the result was multiplied by 100 to obtain the cycle capacity retention rate (%). The results are shown in Table 3.
[0169] The capacity retention rate (%) after 100 cycles was compared with the capacity retention rate (%) after 300 cycles to evaluate the change in the capacity retention rate when the charge-discharge cycle was repeated. Specifically, the change rate (%) of the capacity retention rate from 100 cycles to 300 cycles was calculated as shown in the following formula (3). A large value of this change rate means that the cycle characteristics are greatly deteriorated by the repeated charge-discharge cycles. Fluctuation rate (%) = [(Capacity retention rate after 100 cycles - Capacity retention rate after 300 cycles) / Capacity retention rate after 100 cycles] × 100 (3) The results are shown in Table 3.
[0170] [Table 3]
[0171] As shown in Table 3, each Example satisfied the condition of the following formula (1), and the results of the capacity retention rate, especially the capacity retention rate after 300 cycles, were better than each Comparative Example. [Springback rate x 7.6] + [Compressive load (kN / cm 2 )]≧4.2 (1) Furthermore, as shown in Table 3, it was confirmed that the fluctuation rate (%) of the capacity retention rate from 100 cycles to 300 cycles was smaller in each Example than in each Comparative Example. This shows that the decrease in the cycle capacity retention rate is gradual even when charge / discharge cycles are repeated, due to the decrease in the liquid absorption time index and the increase in the value of the left side of formula (1).
[0172] The disclosure of PCT / JP2021 / 003589, filed February 1, 2021, is incorporated by reference in its entirety into this specification. All publications, patent applications, and standards mentioned in this specification are herein incorporated by reference to the same extent as if each individual publication, patent application, or standard was specifically and individually indicated to be incorporated by reference.
Claims
1. Graphite particles that satisfy the following formula (1): The graphite particles have a compressive load of 2.0 kN / cm 2 or more; The graphite particles have a springback rate of 0.25 or more. [Springback rate × 7.6] + [Compressive load (kN / cm 2 ) ]≧4.2 ... (1)
2. The negative electrode material for lithium ion secondary batteries according to claim 1 , wherein the graphite particles include composite particles having a structure in which a plurality of flat graphite particles are stacked.
3. The springback rate of graphite particles, which are negative electrode materials for lithium ion secondary batteries, and the compression load (kN / cm 2 a regression equation obtained by multiple regression analysis using the above-mentioned formula (1) as an explanatory variable and the liquid absorption time of a negative electrode containing the above-mentioned negative electrode material for a lithium ion secondary battery as an objective variable.
4. A method for producing a negative electrode material for a lithium ion secondary battery, comprising the steps of: producing a negative electrode material for a lithium ion secondary battery based on an evaluation result of the negative electrode material for a lithium ion secondary battery using the evaluation method for a negative electrode material for a lithium ion secondary battery according to claim 3.
5. A method for producing a negative electrode material for a lithium ion secondary battery according to claim 1 or 2, A method for producing a negative electrode material for a lithium-ion secondary battery, comprising the step of graphitizing coke.
6. The thermal expansion coefficient of the coke after firing at 1400°C is 2.30 x 10 -6 The method for producing a negative electrode material for a lithium ion secondary battery according to claim 5, wherein the temperature is 100° C. or higher.
7. A negative electrode for a lithium ion secondary battery, comprising: a negative electrode material layer containing the negative electrode material for a lithium ion secondary battery according to claim 1 or 2; and a current collector.
8. A lithium ion secondary battery comprising the negative electrode for lithium ion secondary batteries according to claim 7, a positive electrode, and an electrolyte solution.
Citation Information
Patent Citations
Carbon material for negative electrode of lithium secondary battery
JP1998326611A
Negative electrode active material for lithium secondary battery, negative electrode including the same and lithium secondary battery
JP2005302725A
Carbonaceous material and method of using same
JP2019508355A
Negative electrode material for lithium-ion secondary cell, method for manufacturing negative electrode material for lithium-ion secondary cell, negative electrode material slurry for lithium-ion secondary cell, negative electrode for lithium-ion secondary cell, and lithium-ion secondary cell
WO2015147012A1
Negative electrode material for lithium-ion secondary cell, method for manufacturing negative electrode material for lithium-ion secondary cell, negative electrode material slurry for lithium-ion secondary cell, negative electrode for lithium-ion secondary cell, and lithium-ion secondary cell
WO2020105196A1